O Programa Minha Casa Minha Vida: política habitacional dos governos Lula e Dilma no período de 2009 a 2014 - Depieri, Marcelo Álvares de Lima (2016)
The objectives of the present study turn to the evaluation of the Program “Minha Casa Minha Vida” (PMCMV) from 2009 to 2014, implemented as a housing policy of the Workers' Party’s in the federal government. Evaluating a policy is always difficult, regardless the situation, given its concrete and latent targets must be investigated. With the arrival of the Workers Party to power the contradictions raised by the policies have become more complex. At the same time that social equalization and access to basic rights measures were implemented to fight poverty, economic and political structures remained, which end up reproducing social inequalities and its effects in Brazilian society. The objective of this study was to investigate whether PMCMV as public policy, proposed by the Workers' Party, was an effective program of access to decent housing for less affluent social classes. In this work it is recognized that housing is accommodation (ceiling, floor and wall), but also its surroundings (infrastructure, landscape and integration with the city). This research aimed to historically contextualize government interventions in the housing and urban field, considering that housing is an important ingredient of the reproduction of the labor force. Besides being an expensive and costly product and accessed by few in the Brazilian social reality, it involves ideological and symbolic aspects, such as the dream of home ownership. In the first chapter a review of the Theory of the Capital was made. This chapter revisited concepts and categories of Karl Marx that contribute to the better understanding of the logic of functioning of capital and current capitalist society and in this case to analyze the Brazilian reality. The second chapter provides an analysis of the program “Minha Casa Minha Vida” from a wider analysis of the Workers Party government. The chapter begins with a presentation of the history of housing policy in Brazil to, over the following pages, analyze Lula and Dilma governments and PMCMV. The third and last chapter presents the empirical part of the study: interviews with residents of the housing complex Teotonio Vilela - Piracicaba, located in Sapopemba neighborhood in São Paulo that was delivered by MCMV in mode “companies” in 2012 and intended to the Track 1 of the program (from 0 to 3 minimum wages). By analyzing the policy from the reality and evaluation of those who are the target audience, along with data of the PMCMV, it was possible to understand how the issue of housing (accommodation and environment) for low income populations is far from a concrete resolution: the construction of houses made by the PMCMV are mostly to families who have income from 3 minimum wages, i.e. middle class, and not for low-income families from 0 to 3 minimum wages. In addition, comfort issues of the apartments for the reality of Brazilian families and the location of many sets far away from urban centers are realities produced by the policy